A dynamic leverage stochastic volatility model - Hoang Nguyen; Trong-Nghia Nguyen; Minh-Ngoc Tran (Örebro University School of Business, 2021)
Stock returns are considered as a convolution of two random processes that are the return innovation and the volatility innovation. The correlation of these two processes tends to be negative which is the so-called leverage effect. In this study, we propose a dynamic leverage stochastic volatility (DLSV) model where the correlation structure between the return innovation and the volatility innovation is assumed to follow a generalized autoregressive score (GAS) process. We founnd that the leverage effect is reinforced in the market downturn period and weakened in the market upturn period.
Keywords: C11; C52; C58; 330; Dynamic leverage; GAS; stochastic volatility (SV)